Progression of IgA Nephropathy under Current Therapy Regimen in a Chinese Population - Li, Xiangling (American Society of Nephrology, 2014)
BACKGROUND AND OBJECTIVES: Current therapy for IgA nephropathy mainly includes renin-angiotensin system inhibitors and adding steroids for patients with persistent proteinuria. This study aimed to evaluate kidney disease progression and its risk factors in a Chinese cohort under current therapy. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Patients with IgA nephropathy followed up for at least 12 months from a prospective database were involved. Renal survival and the relationship between clinical parameters and composite kidney failure events (defined as end stage kidney failure or eGFR halving) were assessed. RESULTS: Overall, 703 patients between 2003 and 2011 were enrolled in this study, with a mean follow-up time of 45 months. Mean eGFR was 84.0 ml/min per 1.73 m(2), systolic BP was 124 mmHg, and time-averaged mean arterial pressure was 90.0 mmHg. Median proteinuria at baseline was 1.60 g/d, and time-averaged proteinuria was 0.80 g/d. The mean rate of eGFR decline was −3.12 ml/min per 1.73 m(2) per year (95% confidence interval, −19.07 to 11.80), and annual end stage kidney failure rate was 2.3%. Multivariate Cox regression analyses revealed that baseline eGFR (hazard ratio, 0.76 per 10 ml/min per 1.73 m(2); 95% confidence interval, 0.66 to 0.91), proteinuria at 6 months (hazard ratio, 1.53 per g/d; 95% confidence interval, 1.27 to 1.84), and systolic BP control at 6 months (hazard ratio, 1.36 per 10 mmHg; 95% confidence interval, 1.05 to 1.77) were associated with composite kidney failure events. Baseline eGFR (regression coefficient, −0.06; 95% confidence interval, −0.07 to −0.04), time-averaged proteinuria (regression coefficient, −0.21; 95% confidence interval, −0.25 to −0.16), and time-averaged mean arterial pressure (regression coefficient, −0.15; 95% confidence interval, −0.21 to −0.09) were independent predictors of the slope of eGFR by linear regression. CONCLUSION: Lower proteinuria and lower BP were associated with slower eGFR decline and lower risk of end stage kidney failure in patients currently being treated for IgA nephropathy.